Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia - Johnson, Jeffrey W.; Wilmer, Jessica Worthington (Zootaxa, 2019)
A new species of epinephelid fish from northeastern Australia is described based on five specimens 408–564 mm SL collected by deep water demersal dropline fishing. Epinephelus fuscomarginatus sp. nov. is known from the Capricorn Channel, off the southern end of the Swain Reefs, Qld, Australia, in depths of 220–230 m. It is distinguished by a combination of dorsal-fin rays XI, 14, pectoral-fin rays 17, anal-fin rays III, 8, caudal-fin rounded, lateral-line scales 60–67, gill rakers 9–10 + 16–19 = 25–28, body depth 3.0–3.4 in SL, angle of preopercle broadly rounded, bearing 4–9 small non-prominent serrae, midlateral part of lower jaw with 2 rows of teeth, tooth patches on vomer and palatines narrow, in 2–3 and 2–4 rows, respectively, and coloration including broad dark brown margins to the soft dorsal, anal and caudal fins. There are no dark spots on the head, body, or fins at any known size and in subadults there are two faint pale brown bars radiating from the eye to the posterior margin of the opercle, and diffuse irregular brown wavy bars and blotches on the sides of the body. Comparison of the mitochondrial cytochrome c oxidase subunit 1 (CO 1) genetic marker utilised in DNA barcoding produced modest but consistent genetic divergences of 1.10% and 2.70 % between E. fuscomarginatus sp. nov. and its closest sampled congeners, E. magniscuttis and E. epistictus, respectively. Further evidence is presented to indicate that populations of E. epistictus currently recognised from the Indian Ocean east to the Indo-Australian Archipelago may be distinct from those from the Sea of Japan to the East China Sea.